Atlas of Infectious Disease Pathology - Schmitt, Bryan H. (Springer International Publishing : Imprint: Springer, 2017)
Infectious diseases may be encountered in nearly every aspect of pathology. This atlas provides an informative reference for the identification of the common and esoteric pathogens, presenting in a wide array of specimen types. The focus of the presented images is on the hematoxylin and eosin-stained appearances of these infections and highlight common special stains that can be used to aid in the diagnosis of the infectious agent. Where appropriate, commentary regarding additional testing such as immunohistochemistry and molecular-based methods is supplied. The Atlas of Infectious Disease Pathology is organized primarily by pathogen type followed by discussion of the various manifestations that may occur in individual organ systems. The reader will be provided with a comprehensive overview of the histopathology of the majority of infectious diseases encountered in general and subspecialty practice alike.
Keywords: Medicine.; Infectious diseases.; Pathology.; elektronické knihy; electronic books